Mixture of CO2-N2 as a potential to SF6 insulation gas: an overview - ., Noor Mazliza; ., Noor Zahirah; ., Muhammad Saufi; Abd-Rahman, Rahisham; Baharom, Md Nor Ramdon (Penerbit UTHM, 2020)
Each equipment in the high voltage (HV) system must retain an appropriate electrical insulation for protection and to avoid any of leakage current [1]. Thus, the choice of insulation material is essential. There are three types of insulation medium which is gases, liquids, and solids. Previous research claims that at normal temperature and pressure, gas insulation was an excellent insulator. An excellent gaseous dielectric material, however, required a long list of demanding properties, for example, having an utmost dielectric strength, good heat transfer, environmental-friendly, high thermal constancy, and available at low cost.